7.1: Invited Paper: Force Touch and Machine Learning Based Smart Sensing Techniques for Interactive Displays. (24th February 2021) - Gao, Shuo; Dai, Yanning; Chen, Junliang; Huang, Anbiao; Liu, Yong
Abstract : Force touch function in interactive displays gains increasing interests due to its ability in detecting 3D information from customers, giving rise to plenty of novel and advanced services for users and therefore increasing the efficiency of human‐machine interactivity. In this article, piezoelectric based force touch architecture and machine learning algorithms are smoothly combined for implementation of user‐centered force level recognition and user identity authentication.